Popular perceptions of tropical ecologists - Putz, F.E. (1996)
There is reason to be concerned about the way we, as scientists and tropical ecologists, are perceived by politicians, entrepreneurs, industrialists, farmers (both wealthy and landless), and, in general, by voters and taxpayers. Our sometimes absurd and generally undeserved public images hinder our capacity to carry out our work. Unless decision-makers and the consumers of our scientific services have confidence in us and recognize the value of our research, our efforts are likely to be unsupported and our recommendations will go unheeded. As scientists we all share the burden of the portrayal of our medieval origins in the dark and smoky caves of the alchemists--transmuters of matter, independent thinkers about causes and origins, practitioners of the black arts, doubters of the divine order as revealed by the Church of Rome, and maniacal pursuers of arcane knowledge tinged with ideological evil. However, the reputation of science and scientists is complex and ebbs and flows, rising during the Renaissance and Age of Discovery, plummeting with our moral stocks after Hiroshima, only to rise again with Sputnik. During any of these periods the general populace often maintained contradictory opinions about the worth of science and the character of scientists; the Atomic Age, for example, was simultaneously a time of hope and a time of despair for the future of our species and the planet. Western society currently seems to be in a love-hate relationship with science and scientists: are we sources of solutions or causes of problems? I believe that as tropical ecologists we need to be concerned about this relationship and endeavor to improve the reputation of scientists in general and tropical ecologists in particular. Unfortunately, working scientists themselves have very little to do with the way we are perceived: Albert Einstein is a prominent exception, but few other practicing scientists influence our public image as much as Drs. Frankenstein, Faustus, Strangelove, and Jekyll (e.g., Haynes 1994). Closer to home we should consider, for example, the archetypal character of the tropical researcher played by Sean Connery in Medicine Man; he is an enchanter, his methods are arcane, and he is obviously obsessed, misanthropic, poorly socialized, and poorly dressed. With the archetype of the colossally arrogant and condescending academic who ruthlessly sacrifices people to gratify scientific curiosity, we need to include the charismatic and intrepid explorer/adventurer type (e.g., Professor Indiana Jones), and the comic bumbler (e.g., the scatologist/wildlife biologist in The Gods Must be Crazy). These media caricatures are compelling, entertaining, and probably unshakable, but we should try to encourage a diversity of depictions that mirrors our actual diversity. The media stereotype of female scientists, in particular, deserves attention. It is extremely disturbing to learn that when 4807 North American school children were asked to draw pictures of scientists, 99.4% of their depictions were middle-aged white males with bad hair or no hair at all, and most of them were working alone on research that was secret, dangerous, or both (Chambers 1983). Why are we perceived this way? Certainly some of us are rightly depicted as male, but bad hair? [no way!] and middle aged? [never!]. I am not suggesting that ATB hire a public relations firm to monitor the media and to assure that we are not being misrepresented, but I think we need to consider how the treatment we receive from the media might predispose people to treat real scientists in ways that we do not deserve. But we should also applaud recent improvements in the way we are portrayed by the media. The scientists in the movie Jurassic Park, for example, are quite informative, diverse, and to Hollywood's standards at least, reasonable. Perhaps as individuals we can most effectively influence the way we are perceived by the public by putting an emphasis on communicating who we are, what we do, and why. Failing to do so limits our opportunities and endangers the society and the planet we serve!